Regulation of the renin-angiotensin-aldosterone system by cyclic nucleotides and phosphodiesterases - Gambaryan, Stepan; Mohagaonkar, Sanika; Nikolaev, Viacheslav O. (Frontiers in Endocrinology, 2023)
The renin-angiotensin-aldosterone system (RAAS) is one of the key players in the regulation of blood volume and blood pressure. Dysfunction of this system is connected with cardiovascular and renal diseases. Regulation of RAAS is under the control of multiple intracellular mechanisms. Cyclic nucleotides and phosphodiesterases are the major regulators of this system since they control expression and activity of renin and aldosterone. In this review, we summarize known mechanisms by which cyclic nucleotides and phosphodiesterases regulate renin gene expression, secretion of renin granules from juxtaglomerular cells and aldosterone production from zona glomerulosa cells of adrenal gland. We also discuss several open questions which deserve future attention.